Seeded growth of zinc oxide thin film and nanostructure by hydrothermal method - Nurul Azzyaty Jayah, 1990- , author; Hafizal Yahaya, supervisor; Abdul Manaf Hashim, supervisor; Institut Teknologi Antarabangsa Malaysia-Jepun (2015)
Thesis (Sarjana Falsafah) - Universiti Teknologi Malaysia, 2015